The Relationship between Nutritional Status and Dysmenorrhea Degree in Female Students of SMA Negeri 1 Surakarta - Kartika, Shinta Amalia; Dewi, Yulia Lanti Retno; Hidayati, Rosalia Sri (Nexus Kedokteran Komunitas, 2014)
Backgrounds : Dysmenorrhea is young women problem. Dysmenorrhea is lower abdominal pain that is felt before or during menstruation. One factor that may lead to primary dysmenorrhea is nutritional status. This study aim is to determine the relationship between nutritional status and degree of dysmenorrhea in female students of SMA Negeri 1 Surakarta. Methods : This research is an observational analytic with cross sectional approach. This research was conducted in SMA Negeri 1 Surakarta. The population was class X female students of SMA Negeri 1 Surakarta who have experienced menstruation period at least 1 year, dysmenorrhea, not smoking, not consuming alcohol, willing to be respondent, L-MMPI scores with the answer "No" < 10, and do not have any gynecological abnormality or secondary dysmenorrhea. Sampling was done by purposive random sampling after selected based on inclusion and exclusion criteria of the study. The dependent variable in this study was the degree of dysmenorrhea, while the independent variable is nutritional status. Research subjects filled (1) informed consent, (2) L-MMPI questionnaire to determine the honesty of respondents in filling out the questionnaire, (3) personal information form and the degree of dysmenorrhea questionnaire, (4) measured height and weight. Ninety two sample was obtained and analyzed using chi-square test followed by Somerâs d correlation test. Results : Based on the data analysis with significance Î± = 0.05, we obtained value of p = 0.004 (p <0.05),Â  whereas correlation coefficient was 0.096. Conclusions : Statistically, there is significant but very weak relationship between nutritional status and dysmenorrhea degree in female students of SMA Negeri 1 Surakarta. Keywords: nutritional status, dysmenorrhea degree